LEFT VENTRAL DIASTOLIC FUNCTIONAMI FEATURES AND SPECIFICITY OF CHANGES IN HEART DISEASE - Roxibjonov A.R. (Web of Journals Publishing, 2023)
AH and IHD are the main causes of LVDD and diastolic HF (Mareev V.Yu., 2003). Violation of LV LV in patients with AH has a multifactorial nature and does not occur in isolation, but simultaneously with a violation of the morphofunctional state of other organs and systems, or with their pathogenetic participation, due to prolonged exposure to high blood pressure.
Keywords: arterial hypertension. arterial pressure, ischemic heart disease, left ventricular ejection fraction.